Reading by Numbers Recalibrating the Literary Field - Bode, Katherine (Anthem Press, 2012)
'Reading by Numbers: Recalibrating the Literary Field' is the first book to use digital humanities strategies to integrate the scope and methods of book and publishing history with issues and debates in literary studies. By mining, visualising and modelling data from 'AustLit' - an online bibliography of Australian literature that leads the world in its comprehensiveness and scope - this study revises established conceptions of Australian literary history, presenting new ways of writing about literature and publishing and a new direction for digital humanities research. The case studies in this book offer insight into a wide range of features of the literary field, including trends and cycles in the gender of novelists, the formation of fictional genres and literary canons, and the relationship of Australian literature to other national literatures.